Statistics Teaching in Adult Education: the inclusion in literacy activities - Keli Cristina Conti; Dione Lucchesi de Carvalho (Educação: Teoria e Prática, 2009)
This paper deals with the deepening of the analysis of a part of the field work of my master’s research in which the focus of study was the teaching and learning of Statistics by adult students of the 7th grade of Elementary school. This episode was chosen after we evaluated what is exemplary to underline the importance of the development of a project called “statistical” for the insertion of these students in literacy activities. We underlined statistic literacy establishing an interlocution with statistical educators who work in this perspective. We also brought authors who have served has a base in our theoretical-methodological framework for the research actions. Moreover, it is worth to underline the vygotskian contribution for the understanding of the mediation of the teacher in Mathematics classes in which Statistics was approached. It is possible to state that the production of the students was beyond the knowledge of Mathematics and Statistics and fulfilled what we intended with regard to the protagonism of those adult students and their inclusion in literacy activities.